Examination of transcriptional networks reveals an important role for TCFAP2C, SMARCA4, and EOMES in trophoblast stem cell maintenance - Kidder, Benjamin L.; Palmer, Stephen

(untitled) (Genome Research, 2010)
Trophoblast stem cells (TS cells), derived from the trophectoderm (TE) of blastocysts, require transcription factors (TFs) and external signals (FGF4, INHBA/NODAL/TGFB1) for self-renewal. While many reports have focused on TF networks that regulate embryonic stem cell (ES cell) self-renewal and pluripotency, little is know about TF networks that regulate self-renewal in TS cells. To further understand transcriptional networks in TS cells, we used chromatin immunoprecipitation with DNA microarray hybridization (ChIP-chip) analysis to investigate targets of the TFs—TCFAP2C, EOMES, ETS2, and GATA3—and a chromatin remodeling factor, SMARCA4. We then evaluated the transcriptional states of target genes using transcriptome analysis and genome-wide analysis of histone H3 acetylation (AcH3). Our results describe previously unknown transcriptional networks in TS cells, including TF occupancy of genes involved in ES cell self-renewal and pluripotency, co-occupancy of TCFAP2C, SMARCA4, and EOMES at a significant number of genes, and transcriptional regulatory circuitry within the five factors. Moreover, RNAi depletion of Tcfap2c, Smarca4, and Eomes transcripts resulted in a loss of normal colony morphology and down-regulation of TS cell–specific genes, suggesting an important role for TCFAP2C, SMARCA4, and EOMES in TS cell self-renewal. Through genome-wide mapping and global expression analysis of five TF target genes, our data provide a comprehensive analysis of transcriptional networks that regulate TS cell self-renewal.